Konsistensi Pengaturan Penetapan Status Bank Gagal Sebagai Penerima Lender Of The Last Resort (LLR) - Ayu Kusuma Ratri (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract __________________________________________________________________ Banking is one of a dominant institution in financial institutions, this needs to the importance of maintain the health bank. One of them with the assistance of the lender last resort (LLR) as a form of aid given to banks which experienced bullying on the soundness of a bank or banks fail. The purpose of the writing of this is analyzed konsitensi regulations on the recipients of assistance lender of the last resorts related to the determination of status and then to analyze lender bank failed arrangement of the last resort for the bank to fail to provide legal certainty. Writing of the method used is normative legal research and kind of approach that is used is the statute approach and conceptual approach. Based on the conclusions can be explained ( 1 ) to determine indicators bank failed to arranged on bank indonesia regulation no 15/ 2 / PBI / 2013 on the provision of the status of banking supervision and the follow-up to conventional public , and based on Memorandum of Understading(MoU) on Cooperation Between The Financial Supervisory Authorities, Central Banks and Financial Ministries of The European Union: On Cross-Border Financial Stability and one  aspect derived from bank Indonesia (2) Bank indonesia need a policy in national banking system in the bank failed to include two things , namely that the mechanism of assistance and legal certainty Key words: bank failed, lender of the last resorts, consi Abstrak __________________________________________________________________ Perbankan merupakan salah satu lembaga yang dominan dalam lembaga keuangan, untuk itu perlu pentingnya menjaga kesehatan bank. Salah satunya dengan bantuan Lender of The Last Resort (LLR) sebagai wujud bantuan yang diberikan kepada bank yang mengalami gangguan pada tingkat kesehatan bank atau bank gagal. Adapun tujuan dari penulisan ini adalah  menganalisa konsitensi peraturan tentang penerima bantuan Lender Of The Last Resort terkait penetapan status bank gagal dan menganalisa  pengaturan Lender Of The Last Resort bagi bank gagal untuk memberikan kepastian hukum. Adapun metode penulisan yang digunakan adalah penelitian hukum normatif dan jenis pendekatan yang digunakan adalah pendekatan perundang- undangan (statute approach) dan pendekatan konseptual (conceptual approach). Berdasarkan hasil kesimpulan dapat dijelaskan (1) Untuk menentukan indikator bank gagal diatur pada Peraturan Bank Indonesia Nomor 15/2/PBI/2013 Tentang Penetapan Status Dan Tindak Lanjut Pengawasan Bank Umum Konvensional, dan berdasarkan  Memorandum of Understading(MoU) on Cooperation Between The Financial Supervisory Authorities, Central Banks and Financial Ministries of The European Union: On Cross-Border Financial Stability dan satu aspek berasal dari Bank Indonesia, (2) Bank Indonesia perlu suatu kebijakan penyempurnaan dalam sistem perbankan nasional pada bank gagal  meliputi 2 hal, yaitu: mekanisme pemberian bantuan dan kepastian hukum.   Kata kunci: bank gagal, lender of the last resort, konsistensi